A state built on sand : how opium undermined Afghanistan - Mansfield, David (Consultant) (Oxford University Press, 2016)
Mansfield's book examines why drug control - particularly opium bans - have been imposed in Afghanistan; he documents the actors involved; and he scrutinizes how prohibition served divergent and competing interests. Above all this book challenges how we have come to understand political power in rural Afghanistan.